2020
DOI: 10.1111/1753-0407.13085
|View full text |Cite
|
Sign up to set email alerts
|

Factors leading to high morbidity and mortality of COVID‐19 in patients with type 2 diabetes

Abstract: Coronavirus disease 2019 (COVID-19) is a recent pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus. Diabetes (mostly type 2 diabetes mellitus, T2DM) and hyperglycemia are among the major comorbidities in patients with COVID-19 leading to poor outcomes. Reports show that patients with diabetes and COVID-19 are at an increased risk for developing severe complications including acute respiratory distress syndrome, multi-organ failure, and death. Here we explore po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(150 citation statements)
references
References 169 publications
3
133
0
14
Order By: Relevance
“…According to the present study, the occurrence of asymptomatic infection is less in COVID-19 patients with diabetes. The compromised immune response among cases with diabetes has been reported to play a role in disease expression and progression [ 26 ] and that can be a strong determinant for the higher frequency of symptomatic COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…According to the present study, the occurrence of asymptomatic infection is less in COVID-19 patients with diabetes. The compromised immune response among cases with diabetes has been reported to play a role in disease expression and progression [ 26 ] and that can be a strong determinant for the higher frequency of symptomatic COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive oxidative stress and impaired immunity (particularly innate cell activity, such as natural killer cells) and pro-inflammatory pathways (including macrophages, T cells, B cells) may increase susceptibility for severe COVID-19 ( 126 , 127 ). The ACE2 receptor for SARS-CoV-2 is highly expressed by adipose tissue, and other relevant tissues [e.g., heart pericytes, pancreatic beta-cells ( 128 )], with adipose tissue a potential reservoir for viral infection ( 125 , 126 ). Entry of the virus may be promoted through pre-existing endothelial dysfunction ( 129 ).…”
Section: Could Uv Light Have Harmful or Beneficial Effects On Covid-1mentioning
confidence: 99%
“…As a rapidly progressing, primarily respiratory viral infection, SARS-CoV-2 elimination from the body seems to be mainly driven by a combination of innate immune response and exhaustion of target cells available for infection 2 . Observational cohort studies published to date have shown that the rate of viral load decline seems slower in older patients, those with more severe disease and those with comorbidities such as diabetes mellitus and immunosuppression [3][4][5][6] . Interpreting these observational studies requires caution because patients have often received antiviral therapies.…”
Section: Introductionmentioning
confidence: 99%